Newly Discovered Miniature Fragments of the “Etchmiadzin Gospel Group” - Manukyan, Seda (Mesrop Mashtots Institute of Ancient Manuscripts)
The study of fragments attached to later manuscripts often brings to light the early stage of Armenian miniature art and creates a basis for new research. Of the over 11,000 Armenian manuscripts kept in the Matenadaran, more than 2,200 contain older fragments used as guard-leaves, of which around 300 are illuminated. Most miniatures are marginal, but there are also fragments containing early examples of Canon Tables and headpieces, as well as portraits of the Evangelists, saints, and military commanders. Rare examples of scenes from the Life of Christ have also been found.
Keywords: Art history